1974
DOI: 10.1139/v74-310
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Gradients in Alkali Halide Molecules

Abstract: . Can. J. Chem. 52,2143Chem. 52, (1974. The electric field gradient q has been calculated from Hartree-Fock wavefunctions for the molecules LiF, LiCI, LiBr, NaF, NaCI, NaBr, KF, and KCI. It is found that o and TC electrons behave quite differently. Exchange distortions are of great importance for a proper understanding of o contributions to q. Polarizations of n electrons into the bonding region are also considerable. These effects are responsible for failures of classical models and are further discussed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…10 for LiF. 36 We note that in the case of LiH, Politzer and Brown" found very little difference between li.p"" and li.p p , while Banyard et al" found them to be quite different.…”
Section: Smith Price and Absar / Pictorial Representationmentioning
confidence: 63%
“…10 for LiF. 36 We note that in the case of LiH, Politzer and Brown" found very little difference between li.p"" and li.p p , while Banyard et al" found them to be quite different.…”
Section: Smith Price and Absar / Pictorial Representationmentioning
confidence: 63%
“…[87] Quantitative use of 7 Li RQCs for structure determination is challenging as -unlike in the case of 2 H -most lithium compounds do not contain more than 1-2 independent 7 Li sites, [88] and the sign of Δν Q is usually not accessible due to absence of resolved 7 Li scalar or dipolar couplings. Recently we proposed a method for structure verification of lithium compounds with rigid organic ligands entailing the following steps: (i) measurement of ligand 13 C, 1 H RDCs and independent determination of A, (ii) construction of model structures with optimised geometry and calculation of V using DFT and (iii) calculation of Δν Q for each model according to Equation 3 and ranking of the structures by comparison to the experimental 7 Li RQC. [89] The method was employed to determine the solvation of lithium chelated by monoanionic bis(benzoxazole-2-yl), bis-(benzothiazole-2-yl) and bis(pyrid-2-yl) methanide ligands in THF-d 8 (Figure 6).…”
Section: LImentioning
confidence: 99%
“…In bonded hydrogen atoms, for example, the 1 s electron can be regarded as spherically symmetric, and the nuclear EFG -and hence the 2 H quadrupole coupling -depends mainly on the effective charge and electronic structure of the direct neighbour. [11] For highly ionic lattices -such as alkali or heavier earthalkali halides -point charges placed at the position of the neighbouring anions give a reasonable qualitative picture of the cationic nuclear EFG, [12] a picture that may be also valid for molecular complexes of these metals with electronegative ligands: [13] Figure 2a shows the lithium EFG of the monomeric lithium amide Li[N(SiMe 3 ) 2 ], where a point charge calculation with a full negative charge on N at a distance of 1.774 Å (3.35 a. u.)…”
Section: Electric Field Gradientmentioning
confidence: 99%
See 2 more Smart Citations